STRONTIUM MOVEMENT INTO PROFILE OF MAURY SILT LOAM SOIL - Yulnafatmawita Yulnafatmawita (Jurnal Solum, 2005)
Groundwater pollution due to chemcal application in agriculture activities has caused much public concerns. Based on the researches having been conducted, it was resulted that chemical leaching in soil frequently showed spatial pattern. Based on the fact, a field research was conducted in Maury silt loam soil (fine, mesic, mixed, Typic Paleudalf) to evaluate spatial variety of Sr movement into and below rooting zone. Chemical material SrCl2.6H2O was evenly distributed on soil surfacein a 18 x18 m plot. Soil samples were taken 4 times (after receiving rainfall 166, 3, 586, and 1085 mm) in 54 locations within the plot. At each sampling undisturbed soil was taken from surface until 100 cm depth, then the Sr element was analyzed from each 10 cm depth. The results showed that there was no spatial pattern found for Sr movement within a 100-cm soil depth in each sampling date. Therefore, based on the analysis of variance, it was about 95% of Sr2+ found on 0-20 cm soil depth even though after receiving 1085 mm rainfall. Key Words: groundwater pollution, agricultural chemicals, spatial structure